Changing Roles in the Pursuit of Alternative Livelihoods among Maasai Agro-Pastoralists in Kenya - Agnes Oywaya-Nkurumwa, (Journal of Agricultural Extension Management, 2025)
The Maasai, traditionally pastoralists, are increasingly pursuing agro-pastoralism as an alternative livelihood. Crop cultivation has introduced new activities and decision-making patterns to the households, which few studies have focused on. This study examines the changing roles of Maasai in their pursuit of alternative livelihoods. The study adopted a cross-sectional survey research design. Data were collected through interviews, from 153 male and 87 female household heads Jn Narok North Sub-county, Kenya. The study found that more females than males were involved in planting, weeding and harvesting while more males were involved in marketing crop produce. Women's involvement in marketing was higher than in pastoralism where they rarely participated. Men made most decisions on crop farming activities, although women's involvement was substantial. The study concludes that agro-pastoralism has led to changed roles among Maasai men and women, and, women bore a heavier labour burden. Crop farming also led to empowerment and improved status of women due to their involvement in marketing, income generation and decision-making. The challenge for the extension service is to provide appropriate support to the Maasai agro-pastoralists in the face of their changing roles, so that they can successfully diversify their livelihoods for improved household food security and incomes